SEGMENTATION OF TOUCHING LANNA CHARACTERS - Sakkayaphop Pravesjit; Arit Thammano (My University, 2011)
Character segmentation is an important preprocessing step for character recognition. Incorrectly segmented characters are not likely to be correctly recognized. Touching characters is one of the most difficult segmentation cases which arise when handwritten characters are being segmented. Therefore, this paper emphasizes the interest to the segmentation of touching and overlapping characters. In the proposed character segmentation process, the bounding box analysis is initially employed to segment the document image into images of isolated characters and images of touching characters. The thinning algorithm is applied to extract the skeleton of the touching characters. Next, the skeleton of the touching characters is separated into several pieces. Finally, the separated pieces of the touching characters are put back to reconstruct two isolated characters. The proposed algorithm achieves an accuracy of 75.3%.
Keywords: Minimum bounding box; Bounding overwatch; Vehicle License Plate Recognition